Oral communicative needs of frontliners at international student centres / Ahmed Z D Razaiyneh - Ahmed Z D, Razaiyneh (2017)
This study identifies the English language needs of the frontliners of international student centres (ISC) of the highest ranked public universities in Malaysia and determines what is required for them to accomplish their job functions efficiently and effectively. More specifically, this study aims to suggest the appropriate steps and methods required to overcome the communicative language problems encountered by ISC frontliners. It focuses on the oral communicative sub-skills used during interaction with international students. This study uses the concurrent triangulation strategy using quantitative and qualitative approaches to cross validate, corroborate the findings, and to complement the weaknesses and strengths of the two methods. Questionnaires, semi-structured interviews and focus group discussions are used to gather information for this research. The findings of the study indicated that most of the ISC frontliners seemed to show similarities with their perceived English language needs. The staff considered listening and speaking skills as the two most required skills for them to perform their required job functions efficiently. Most of the ISC frontliners stated that the most important skills are oral communicative skills and the ability to communicate effectively with students. The findings revealed that ISC frontliners require more improvement in the proficiency and fluency in speaking skills such as speaking with the correct pronunciation and intonation, conveying messages, and explaining instructions clearly and accurately. In addition, it is vital that the ISC frontliners improve their interactive skills such as asking questions and confirming details, offering alternatives, negating requests, and adopting turn-taking strategies. The findings showed that the majority of ISC frontliners were positive towards the need for an English language course to help them improve their English language proficiency. Based on the findings, a two hour weekly, 14 weeks, intermediate course for ISC frontliners was developed.